APLIKASI KETERAMPILAN KOMUNIKASI KONSELOR DALAM PROSES KONSELING DI SMP NEGERI KOTA MADIUN - Widodo, Bernardus (Widya Warta, 2012)
Guidance and Counseling Services in school are the services which are personal approach and group approach in nature. Individual counseling is a service which is personal approach. In its implementation, individualized counseling requires that a counselor has the ability and skills in using facilitative responses for the attainment of the goals of counseling. Cormier & Cormier, (1991) and Brammer (in Romlah 2001) classify facilitative responses in the counseling relationship into several basic communication skills of counseling such as: opening, acceptance, structuring, reflection of feelings,Â  reflection of meaning, restatement, clarification, paraphrasing, confronting, questioning, reassurance, exploration, summary,advice, rejection, termination, focussing, minimum encouragement, exploration, and directing.Recognizing the importance of communication skills in counseling, the researcher focussed his study on the application of several communication skills in counseling by acounselor, whose general aim is to know how the basic communication skills in counseling are applied by counselors, especially school counselors of Junior High Schools in Madiunmunicipality.This research is descriptive with a sample of some 30 state junior high school counselors in Madiun municipality. The analysis of data showed that the average score of the application of overall basic counseling skills is 2.48, which is classified as good. In detail, of the 15 applications of basic counseling skills, a conclusion can be drawn as follows: (a) five of them are classified as excellent, namely skills of opening (mean 3.30), acceptance (mean 3.23), termination (mean 3.25), reassurance (mean 3.20), and structuring (mean 3.15), (b) four of them are classified as good, namely skills of reflection of feelings (mean 2.24), questioning/lead (mean 2.50 ), summary (mean 2.82), and rejection (mean 2.66), (c) six of them are classified as enough, namely skills of restatement (mean 1.97), clarification (mean 1.85), reflection of meaning (mean 2.00), confrontation (mean 1.59), paraphrasing (mean 1.95), and advice (mean1.47).